ANALISIS PENGARUH PENERAPAN MANAJEMEN STRATEGIK DAN PENYUSUNAN ANGGARAN PEMILUKADA TERHADAP KINERJA LEMBAGA PENYELENGGARA PEMILU - Agus Defri Yando; Syarif Hidayah Lubis (LPPM Universitas Putera Batam, 2019)
KPU in the city of Batam is a state institution that organizes public services in the ownership sector. In planning its duties and functions, KPU Batam has compiled a strategic plan, annual work plan and performance agreement. The implementation of strategic management and budget preparation is considered to affect the performance of the institutions both financial performance and program performance. This research is a quantitative descriptive study with a correlational approach. The variables tested in this study were the application of Stratejic management and budget drafting as independent variables and performance achievements as dependent variables. This research uses secondary data consisting of institutional documents in the form of strategic plan comments, annual work plans, performance reports and budget realization. This research shows that the variable (X1) is the application of strategic management that is engaged towards the performance of the board. Variable (X2) Implementation of budget drafting that affects the institution's performance.